Mechanical and structural property analysis of bacterial cellulose composites. (25th June 2016) - Dayal, Manmeet Singh; Catchmark, Jeffrey M.
Highlights: Culturing bacterial cellulose with pectin or gelatin improves its mechanical behavior. The addition of pectin increased the compressive modulus by a factor of ∼20. Improved compression behavior is attributed to increasing the bound water content. Abstract: Bacterial cellulose (BC) exhibits unique properties including high mechanical strength and high crystallinity. Improvement in the mechanical properties of BC is sought for many applications ranging from food to structural composites to biomedical materials. In this study, different additives including carboxymethyl cellulose (CMC), pectin, gelatin, cornstarch, and corn steep liquor were included in the fermentation media to alter the BC produced. Three different concentrations (1%, 3% and 5%) were chosen for each of the additives, with no additive (0%) as the control. The produced BC was then analyzed to determine tensile and compression modulus. Amongst the tested additives, BC produced in media containing 3% (w/v) pectin had the maximum compressive modulus (142 kPa), and BC produced in media containing 1% (w/v) gelatin exhibited the maximum tensile modulus (21 MPa). Structural characteristics of BC and BC-additive composites were compared using X-Ray diffraction (XRD). The crystal size and crystallinity of BC was reduced when grown in the presence of CMC and gelatin while pectin only decreased the crystallite size. This suggested that CMC and gelatin may be incorporated into the BC fibril structure. The field emission scanning electron microscopy (FESEM) images showed the increased micro-fibril aggregation in BC pellicles grown in the presence of additives to the culture media.